Comparative Review of Smart Housing Strategies for Aging Populations in South Korea and the United Kingdom - Suyee Jung (Buildings)
As populations age globally, governments face mounting challenges in reconfiguring healthcare and housing systems to support aging-in-place. This study offers a comparative analysis of South Korea and the United Kingdom, examining how each country integrates digital technologies, such as Artificial Intelligence (AI), telecare, and smart housing systems, into their aging strategies. South Korea employs a centralized, technology-driven approach that prioritizes the national rollout of AI-enabled smart homes and digital health infrastructure. In contrast, the UK advances a decentralized, community-based model emphasizing social housing, localized care delivery, and telecare integration. Despite these differing trajectories, both nations face shared limitations, including high implementation costs, digital literacy barriers, and concerns about data privacy. Critically, the study finds that the success of aging-in-place efforts is shaped not only by technological capacity but also by governance dynamics, political continuity, and institutional coordination. In response, the paper proposes policy recommendations alongside an ethical framework grounded in transparency, autonomy, informed consent, and equity. Sustainable aging-in-place strategies require not only innovative technologies, but also inclusive governance and ethically robust design to ensure accessibility, trust, and long-term impact.